2017
DOI: 10.18632/aging.101262
|View full text |Cite
|
Sign up to set email alerts
|

Aging and sarcopenia associate with specific interactions between gut microbes, serum biomarkers and host physiology in rats

Abstract: The microbiome has been demonstrated to play an integral role in the maintenance of many aspects of health that are also associated with aging. In order to identify areas of potential exploration and intervention, we simultaneously characterized age-related alterations in gut microbiome, muscle physiology and serum proteomic and lipidomic profiles in aged rats to define an integrated signature of the aging phenotype. We demonstrate that aging skews the composition of the gut microbiome, in particular by alteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 50 publications
3
105
0
Order By: Relevance
“…The existence of a gut microbiota profile associated with sarcopenia and involving changes in the abundance of health-related Bifidobacteria has previously been shown in rats [43]. While very little is known about a possible functional link between Oscillospira and PF&S, the existence of a trait for butyrate-producing bacteria Ruminococcus is in-keeping with previously reported associations between Ruminococcus abundance and frailty [40].…”
Section: Discussionsupporting
confidence: 80%
“…The existence of a gut microbiota profile associated with sarcopenia and involving changes in the abundance of health-related Bifidobacteria has previously been shown in rats [43]. While very little is known about a possible functional link between Oscillospira and PF&S, the existence of a trait for butyrate-producing bacteria Ruminococcus is in-keeping with previously reported associations between Ruminococcus abundance and frailty [40].…”
Section: Discussionsupporting
confidence: 80%
“…The microbiota can also influence muscle mass, as reported by Ticinesi et al [13]. Sarcopenia rat models exhibit a reduction of several taxa with anti-inflammatory and pro-anabolic effects in gut microbiota [14]. To compensate for their increased energy consumption and maximize their adaptation to physical loads, athletes must adopt adequate dietary habits, which increasingly include a broad range of sports nutritional supplements.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a gut-muscle axis in the pathogenesis of age-related sarcopenia in humans has been proposed recently based on very promising results(67). The interplay between microbiome and skeletal muscle has been highlighted by Siddhart and colleagues(64) who demonstrated that age-related changes of gut microbiome are associated with the physiological decline of musculoskeletal function. Future studies will be needed to identify the bacterial species and/or the underlying mechanisms and the putative metabolites that contribute to the functional link between gut microbiota and skeletal muscle.…”
mentioning
confidence: 99%